The Structural Relationships of Emotional Neglect with Risky Behaviors in Prisoners Considering the Mediating Role of Emotion Regulation Strategies - Ershadi Manesh , Soudabeh; Kafi Malak , Sara (Health Nexus, 2025)
This study aimed to investigate the structural relationships of emotional neglect with risky behaviors in prisoners, considering the mediating role of emotion regulation strategies. The research method is descriptive-correlational. The statistical population consists of all prisoners in the city of Shiraz. The research sample included 409 prisoners from Shiraz, selected through purposive sampling. Data were collected using the Childhood Trauma Questionnaire (Bernstein et al., 2003), the Cognitive Emotion Regulation Questionnaire (Garnefski et al., 2001), and the Youth Risk Behavior Scale (Snow et al., 2019). Structural equation modeling (SEM) was conducted using AMOS 24 and SPSS 27 to evaluate the proposed model. The correlation coefficient results indicated a negative relationship between emotional neglect and adaptive cognitive emotion regulation strategies with risky behaviors (P ≤ 0.05). Additionally, there was a significant positive relationship between maladaptive cognitive emotion regulation strategies and risky behaviors (P ≤ 0.05). The findings suggest an adequate fit of the proposed model with the data. The results of the structural model showed that 25% of the variance in adaptive cognitive emotion regulation strategies and 30% of the variance in maladaptive cognitive emotion regulation strategies were explained by emotional neglect. Furthermore, 44% of the variance in risky behaviors was explained by emotional neglect, adaptive, and maladaptive cognitive emotion regulation strategies. Based on these findings, early intervention and preventive measures are crucial in reducing the negative impact of emotional neglect. Specifically, focusing on interventions based on mentalization and emotion regulation can significantly improve emotional and relational problems arising from adverse early life experiences.